Analysis of Simplex Machine Damage Using Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) Methods - Nurfadhilah, Annisa; Hermawan, Asep; Sofyan, Hady (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
The current industrial landscape is experiencing rapid development, compelling companies to produce high-quality products that meet consumer expectations. The production activities are crucial in the execution of the production process, and smooth operations are highly anticipated by companies in general. This study aims to identify the root causes of frequent breakdowns in the simplex machine that occurred between February and April 2023. The study employs the Fault Tree Analysis (FTA) method to determine the root causes of issues that lead to undesirable events. The results from the Fault Tree Analysis revealed that the primary causes of simplex machine breakdowns are attributed to human factors, machine issues, and material problems. Furthermore, the findings from the Failure Mode and Effect Analysis (FMEA) identified the highest Risk Priority Numbers (RPN) for each component: lack of scheduled machine maintenance (RPN = 192), old machinery (RPN = 64), and waste material getting stuck in the flayer (RPN = 210).